2001
DOI: 10.1074/jbc.m103776200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent Kinase 5 Promotes Insulin Exocytosis

Abstract: Cyclin-dependent kinase 5 (Cdk5) is widely expressed although kinase activity has been described preferentially in neuronal systems. Cdk5 has an impact on actin polymerization during neuronal migration and neurite outgrowth and deregulation of the kinase has been implicated in the promotion of neurodegeneration. Recently it was shown that Cdk5 modulates dopamine signaling in neurons by regulating DARPP-32 function. In addition, Cdk5 phosphorylates munc-18 and synapsin I, two essential components of the exocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 73 publications
4
76
2
1
Order By: Relevance
“…It would seem that other molecules are involved in GTP-mediated secretion, but it also seems that participation of Cdk5-p35 is crucial to reach the maximum GTP-triggered secretory response. Our observations parallel a previous report that Cdk5-p35 acts as a positive regulator of insulin secretion from pancreatic ␤ cells (32). Roscovitine or dominant-negative Cdk5 expression inhibits calcium-independent ␤ cell secretion.…”
Section: Discussionsupporting
confidence: 80%
“…It would seem that other molecules are involved in GTP-mediated secretion, but it also seems that participation of Cdk5-p35 is crucial to reach the maximum GTP-triggered secretory response. Our observations parallel a previous report that Cdk5-p35 acts as a positive regulator of insulin secretion from pancreatic ␤ cells (32). Roscovitine or dominant-negative Cdk5 expression inhibits calcium-independent ␤ cell secretion.…”
Section: Discussionsupporting
confidence: 80%
“…There is presently a substantial amount of data to indicate that CDK5 plays important roles in extraneuronal cells during the process of myogenesis, lens differentiation, spermatogenesis, insulin secretion, apoptosis of ovarian cells and hematopoietic cell differentiation. 3,[5][6][7][8][9][10][11] Furthermore, CDK5 has been suggested to play roles in the regulation of motility of prostate cancer cells, 12 control of glioblastoma cell invasion, 13 modulation of proliferation of medullary thyroid carcinoma cells 14 and apoptotic control of leukemia cells. 15 These potential roles of CDK5 activity in the carcinogenesis of each cell type seem to involve distinct target substrates.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that Cdk5 is present in pancreatic ␤-cells where it acts as a positive regulator of insulin secretion (32). The goals of the present study were to investigate the expression, subcellular distribution and potential roles of p35 and p39 in Cdk5-mediated insulin secretion.…”
mentioning
confidence: 99%
“…Furthermore, several lines of research have suggested that some synaptic proteins, such as Munc18-1 and synapsin 1 are substrates for Cdk5 (20,30,31). Intriguingly, Cdk5 has been demonstrated to have the ability to both promote regulated exocytosis of insulin and function as a negative regulator of dopaminergic and glutamatergic transmission in the striatum (32,33). Moreover, Cdk5 was recently identified as a dephosphin kinase, essential for synaptic vesicle endocytosis, establishing Cdk5 as a key controller of membrane trafficking in nerve terminals (34 -36).…”
mentioning
confidence: 99%